Menstimulus Perkembangan Motorik Kasar Anak Melalui Permainan Engklek dl Kober Miftahul Fallah - Mutiara Aulia; Salsa Fadila; Eha Solehah; Intan Permata Sari (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Gross motor skills in children are important to train, especially in the early years of school, one way to stimulate gross motor skills in children, namely; through traditional engklek games in improving gross motor skills in early childhood descriptive research methods with a qualitative approach used in this study. The results showed that the implementation of the engklek game at Kober Miftahul Fallah Cibenda, Parigi, Pangandaran is carried out regularly once a month, the game still uses natural media in the form of an arrangement of plots with numbers and the APE used is in the form of tile fragments as gacuk. Kober Miftahul Fallah prefers traditional games in the form of cricket to modern games, they do this with the aim of reviving the traditional game of cricket so that it is more sustainable and trying to campaign or socialize that this cricket game is not only not playing but there is an element of education in children. Indirectly, besides being able to hone children's gross motor skills, this game can also train communication skills, process emotions, train body balance and empathize, so that students will have strong capital to explore and make friends in their new environment. In its implementation, the teacher makes an assessment of the development of students to see the extent of children 's gross motor skills in traditional games.